Geopathogenic zones and oncological morbidity of the population - M. P. Hrebniak; O. V. Kirsanova; V. V. Taranov (Zaporožskij Medicinskij Žurnal)
The aim of the work is to establish the effect of a geopathogenic zone on the cancer incidence in the population.